ESG Orientation and Corporate Innovation Performance: Structural Equation Modeling of Organizational Learning Capability in ASEAN Manufacturing Firms - Somchai Prasert (Kalam Practica Media, 2026)
This research evaluates the structural relationships linking environmental, social, and governance orientation to corporate innovation performance, specifically testing the underlying mediating function of organizational learning capability within manufacturing networks. Confirmatory covariance-based structural equation modeling via IBM SPSS AMOS 26 software was executed on a cross-sectional dataset matching secondary sustainability index scores with primary survey disclosures from 412 large-scale manufacturing firms across Indonesia, Malaysia, Thailand, and Vietnam. The empirical findings confirmed that Environmental, Social, and Governance (ESG) Orientation exerts a significant positive effect on Organizational Learning Capability (β = 0.542, p < 0.001) and Corporate Innovation Performance (β = 0.218, p < 0.01). Organizational Learning Capability also demonstrated a strong positive influence on Corporate Innovation Performance (β = 0.476, p < 0.001) and significantly mediated the relationship between ESG Orientation and Corporate Innovation Performance (β = 0.258, p < 0.001). Furthermore, the proposed structural model achieved satisfactory goodness-of-fit, with χ²/df = 1.842, Comparative Fit Index (CFI) = 0.968, Tucker-Lewis Index (TLI) = 0.963, and Root Mean Square Error of Approximation (RMSEA) = 0.044, indicating that the model adequately represents the observed data.